Pengendalian Penyakit Layu Fusarium Pada Pisang Dengan Inokulasi Jamur Mikoriza Vesikular Arbusicular Pada Bibit = Control Of Fusarium Wilt On Banana Used Seedling Was Inoculated Vesicular Arbuscular Mycorrhiza - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Abstract: Fusarium wilt disease caused by Fusarium oxysporumfsp. cubense is the most important and destructive disease on banana. The pathogen is soil borne and can survive in soil without the occurence of the host. The Vesicular Arbuscular Mychorriza {YAM) is a symbiotic associated fungi and plant roots. The VAMwhich infected plant can induce the resistance to pathogen. Banana seedlings obtained from tissue culture one free from pathogen. The seedling was inoculated with VAM to induce the resistance to Fusarium wilt disease. The result showed that the seedling inoculated with VAM can reduce diseases intensity ofFusarium wilt on banana.